Depth distribution of irradiation-induced cross-linking in aromatic self-assembled monolayers - Tai, Y (Langmuir : the ACS journal of surfaces and colloids, 2004)
Pristine and strongly irradiated self-assembled monolayers of [1,1':4',1' '-terphenyl]-4,4' '-dimethanethiol (TPDMT) on Au have been characterized by near-edge X-ray absorption fine structure spectroscopy using partial electron yield acquisition mode. The TPDMT films were found to be extremely stable toward electron irradiation, which is explained by cross-linking between the aromatic backbones. In addition, we assume that a large delocalization and a strong relaxation of the initial electronic excitations in the densely packed film contributed to the film stability. The data analysis implies an inhomogeneous distribution of the irradiation-induced dehydrogenation and cross-linking of the terphenyl moieties in the TPDMT film, being most pronounced close to the film-ambient interface. The inhomogeneity was explained by quenching of the electronically excited C-H states via dipole-dipole interaction with the states' image at the metal surface, which has a reduced probability with increasing separation from the metal surface. Generally, the results suggest the importance of relaxation processes for the response of self-assembled monolayers to ionizing radiation